New device for assessing the toe-brachial index and a pilot cross-sectional study in diabetic patients - Thiago Paes de Barros De Luccia; Alexandre Donisete Bensi; Nelson De Luccia; Priscilla Matos Cunha; Lia Maristela da Silva Jacob; Leonardo Servato Sanches Martins de Barros; Julio Maganha Gouvêa; Vívian Mei Matuoka (Jornal Vascular Brasileiro)
Abstract Background Blood pressure measurements in the hallux and fingers are important in evaluation of patients with diabetes, obese patients, dialysis patients, and those with peripheral artery disease. Objectives In this article, we tested a prototype of an automatic device for measuring systolic pressure in fingers and toes, combining optical plethysmography and a pressure sensor, with a cuff encircling the finger or toe, and controlled by a microcontroller. Methods The prototypes (a total of 3 identical devices) were tested for initial validation (with a group of participants who already had symptoms of peripheral arterial disease [PAD], n=30) and also in clinical comparisons between controls (n=15) and participants with diabetes (n=15). The following variables were tested: Ankle-brachial index; Toe-finger index; Toe-brachial index, and toe pressure in isolation. For validation, the toe pressure in isolation was measured with two devices (the prototype under test and the SysToe® device), to analyze the correlation between the two measurements. Results The correlation between the two devices was strong (R=0.88) in the group with symptoms of PAD. Toe-brachial index was lower in patients with diabetes than in control participants (p=0.005) as was the Toe-finger index (p=0.03), however, the Ankle-brachial index was similar in these two groups (p=0.92). Conclusions The findings show the feasibility of the device for measuring finger and toe pressures, and possibly indicate greater sensitivity for detecting early-stage arterial disease using this type of measurement.